Vaksinasi Rabies oleh Abdi Nusantara XIII FKH IPB Bersama Dinas Pertanian Kota Padang - Silvia Anggraini; Ni Wayan Kurniani Karja (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Rabies is a zoonotic disease with a Case Fatality Rate (CFR) or the mortality rate reaches 100%. One of the transmissions of rabies in West Sumatra is influenced by the tradition of hunting pigs. In West Sumatra during 2013-2016 as many as 16 people died due to rabies. This activity aims to assist the Department of Agriculture in realizing freedom of Padang from rabies infectious diseases. This activity uses the method of observation with active participation. The results of the rabies vaccination activities in Padang were 99 vaccinated rabies animals. Of the 99 animals, 9 of them are dogs and 90 cats. Keywords: Padang City, rabies, zoonosis